Cavernous antioxidant effect of green tea, epigallocatechin‐3‐gallate with/without sildenafil citrate intake in aged diabetic rats. (29th August 2012) - Mostafa, T.; Sabry, D.; Abdelaal, A. M.; Mostafa, I.; Taymour, M.
Summary This study aimed to assess the cavernous antioxidant effect of green tea (GT), epigallocatechin‐3‐gallate (EGCG) with/without sildenafil citrate intake in aged diabetic rats. One hundred and four aged male white albino rat were divided into controls that received ordinary chow, streptozotocin (STZ)‐induced aged diabetic rats, STZ‐induced diabetic rats on infused green tea, induced diabetic rats on epigallocatechin‐3‐gallate and STZ‐induced diabetic rats on sildenafil citrate added to EGCG. After 8 weeks, dissected cavernous tissues were assessed for gene expression of eNOS, cavernous malondialdehyde (MDA), glutathione peroxidase (GPx), cyclic guanosine monophosphate (cGMP), and serum testosterone (T). STZ‐induced diabetic rats on GT demonstrated significant increase in cavernous eNOS, cGMP, GPx and significant decrease in cavernous MDA compared with diabetic rats. Diabetic rats on EGCG demonstrated significant increase in cavernous eNOS, cGMP, GPx and significant decrease in cavernous MDA compared with diabetic rats or diabetic rats on GT. Diabetic rats on EGCG added to sildenafil showed significant increase in cavernous eNOS, cGMP and significant decrease in cavernous MDA compared with other groups. Serum T demonstrated nonsignificant difference between the investigated groups. It is concluded that GT and EGCG have significant cavernous antioxidant effects that are increased if sildenafil is added.